2016
DOI: 10.1038/srep29927
|View full text |Cite
|
Sign up to set email alerts
|

Two fatty acyl reductases involved in moth pheromone biosynthesis

Abstract: Fatty acyl reductases (FARs) constitute an evolutionarily conserved gene family found in all kingdoms of life. Members of the FAR gene family play diverse roles, including seed oil synthesis, insect pheromone biosynthesis, and mammalian wax biosynthesis. In insects, FAR genes dedicated to sex pheromone biosynthesis (pheromone-gland-specific fatty acyl reductase, pgFAR) form a unique clade that exhibits substantial modifications in gene structure and possesses unique specificity and selectivity for fatty acyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 48 publications
2
30
2
2
Order By: Relevance
“…Later studies reported the roles of these enzymes in the production of sex pheromones. Subsequently, FAR s were reported in many other lepidopteran species (Antony, Ding, Moto, Aldosari, & Aldawood, ; Hagström, Liénard, Groot, Hedenström, & Löfstedt, ; Lassance et al., ; Lassance et al., ). Some pheromone‐gland‐specific FAR s ( pgFAR s) reduce a broad range of saturated or unsaturated fatty acids to corresponding fatty alcohols in sex‐pheromone biosynthesis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Later studies reported the roles of these enzymes in the production of sex pheromones. Subsequently, FAR s were reported in many other lepidopteran species (Antony, Ding, Moto, Aldosari, & Aldawood, ; Hagström, Liénard, Groot, Hedenström, & Löfstedt, ; Lassance et al., ; Lassance et al., ). Some pheromone‐gland‐specific FAR s ( pgFAR s) reduce a broad range of saturated or unsaturated fatty acids to corresponding fatty alcohols in sex‐pheromone biosynthesis.…”
Section: Introductionmentioning
confidence: 97%
“…Some pheromone‐gland‐specific FAR s ( pgFAR s) reduce a broad range of saturated or unsaturated fatty acids to corresponding fatty alcohols in sex‐pheromone biosynthesis. Some pgFAR s show a wide range of functional flexibility (Antony et al., ; Liénard & Löfstedt, ). The honey bee AmFAR1 and Drosophila waterproof are similarly flexible.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the findings available to date suggest that the FARs in general exhibit diverse substrate specificities with respect to the fatty acyl chain length and unsaturation state of the substrate. The pool of fatty acyls available for reduction in the host organism can also influence the apparent FAR specificity [111][112][113].…”
Section: Far Propertiesmentioning
confidence: 99%
“…In silk moth (Bombyx mori), researchers discovered a pheromone gland-specific FAR [118] that is able to convert E10,Z12-16:2 FA precursor to the corresponding alcohol bombykol, the main component of the female sex pheromone. Since then, a range of moth pheromone-biosynthetic FARs have been isolated and functionally characterized [89,111,[119][120][121][122][123] (Table 2). Although moth FARs usually exhibit a broad substrate preference [77,89,111,120,122,123], some of them display specificity to unsaturated substrates with a double bond in either the E or Z configuration [119], a particular chain length and double bond position [120], or a system of conjugated double bonds [118].…”
Section: Far Propertiesmentioning
confidence: 99%
See 1 more Smart Citation